EFFECT OF PARTLY AIR BLOCAGE IN AXIAL COMPRESSOR ON SURGE AND OUTPUT - Ju A Antipov; I K Shatalov; E R Ramazanov; A D Tuzikov (RUDN Journal of Engineering Research, 2016)
Effect of partly air blockage in axial compressor on surge and output. The tests show, that partly air blockage of compressor inlet by the mean of special diaphragms allow instantly expel the surge and diminish output on 40%.